Maternal Prepregnancy Body Mass Index and Risk of Spontaneous Preterm Birth. Issue 4 (9th May 2014) - Shaw, Gary M.; Wise, Paul H.; Mayo, Jonathan; Carmichael, Suzan L.; Ley, Catherine; Lyell, Deirdre J.; Shachar, Bat Zion; Melsop, Kathryn; Phibbs, Ciaran S.; Stevenson, David K.; Parsonnet, Julie; Gould, Jeffrey B.; et al.
Abstract Background Findings from studies examining risk of preterm birth associated with elevated prepregnancy body mass index (BMI) have been inconsistent. Methods Within a large population‐based cohort, we explored associations between prepregnancy BMI and spontaneous preterm birth across a spectrum of BMI, gestational age, and racial/ethnic categories. We analysed data for 989 687 singleton births in California, 2007–09. Preterm birth was grouped as 20–23, 24–27, 28–31, or 32–36 weeks gestation (compared with 37–41 weeks). BMI was categorised as <18.5 (underweight); 18.5–24.9 (normal); 25.0–29.9 (overweight); 30.0–34.9 (obese I); 35.0–39.9 (obese II); and ≥40.0 (obese III). We assessed associations between BMI and spontaneous preterm birth of varying severity among non‐Hispanic White, Hispanic, and non‐Hispanic Black women. Results Analyses of mothers without hypertension and diabetes, adjusted for age, education, height, and prenatal care initiation, showed obesity categories I–III to be associated with increased risk of spontaneous preterm birth at 20–23 and 24–27 weeks among those of parity 1 in each race/ethnic group. Relative risks for obese III and preterm birth at 20–23 weeks were 6.29 [95% confidence interval (CI) 3.06, 12.9], 4.34 [95% CI 2.30, 8.16], and 4.45 [95% CI 2.53, 7.82] for non‐Hispanic Whites, non‐Hispanic Blacks, and Hispanics, respectively. A similar, but lower risk, pattern was observed for women of parity ≥2 and preterm birth at 20–23 weeks. Underweight was associated with modest risks for preterm birth at ≥24 weeks among women in each racial/ethnic group regardless of parity. Conclusions The association between women's prepregnancy BMI and risk of spontaneous preterm birth is complex and is influenced by race/ethnicity, gestational age, and parity.